1998
DOI: 10.1159/000030956
|View full text |Cite
|
Sign up to set email alerts
|

Point Mutations and Deletion Responsible for the Bombay H null and the Reunion H weak Blood Groups

Abstract: Objective: Definition of the molecular basis of the Reunion and the Bombay red cell and salivary H-deficient phenotypes. Methods: Sequence and expression of FUT1 and FUT2 genes from H-deficient individuals. Family segregation analysis of the mutations responsible for the fucosyltransferase defects of H, secretor and Lewis systems. Results: The Indian red cell H null Bombay phenotype depends on a new mutation of the FUT1 gene. T725 → G changing Leu242 → Arg. Their salivary nonsecretor phenotype is secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(50 citation statements)
references
References 25 publications
2
47
0
1
Order By: Relevance
“…The PCR reactions were run in 15 µl with 5µl of each primer mix ( The FUT3 PCR-SSP assay was initially developed on DNA samples from blood donors, not included in this study but with known FUT3 genotypes [Elmgren et al, 1996;Fernandez-Mateos et al, 1998]. The final design of each primer-pair is shown in Tables 1 and 2.…”
Section: Pcr-ssp Genotyping Of Fut2 and Fut3 Mutationsmentioning
confidence: 99%
“…The PCR reactions were run in 15 µl with 5µl of each primer mix ( The FUT3 PCR-SSP assay was initially developed on DNA samples from blood donors, not included in this study but with known FUT3 genotypes [Elmgren et al, 1996;Fernandez-Mateos et al, 1998]. The final design of each primer-pair is shown in Tables 1 and 2.…”
Section: Pcr-ssp Genotyping Of Fut2 and Fut3 Mutationsmentioning
confidence: 99%
“…In addition, we have reported three recombinant FUT2 alleles as nonfunctional alleles : one was the fusion gene (se fus ), consisting of the 5h region of a pseudogene of FUT2 (Sec1) and the 3h region of the FUT2 in Japanese individuals (Koda et al 1996 ;Liu et al 1999), while the other two were distinct and included complete deletion of the FUT2 (se del and se del# ) generated by Alu-Alu recombination (Koda et al 1997Pang et al 2000). The se del was originally identified in Indian individuals with the classical Bombay phenotype (Koda et al 1997 ;Fernandez-Mateos et al 1998) and also recently found in a Bangladeshi population with a high frequency (0n074) (Pang et al 2000). The se del# has been found in Samoans (Pang et al 2000).…”
mentioning
confidence: 99%
“…One nonfunctional allele, se 6 , is the result of a fusion gene between FUT2 (ie, Se) and the adjacent upstream Sec1 pseudogene. 86,87 This large deletion is mediated by the presence of Alu sequences, 88 many of which are present in this chromosomal region. Finally, the complete deletion of the entire FUT2 gene is seen in individuals with the classical Bombay phenotype (see below); this allele is denoted as se del .…”
Section: Blood Group Secretions (Type 1 Chain) Red Cells (Type 2 Chain)mentioning
confidence: 99%